PROSPECTS FOR THE USE OF THORIUM IN NUCLEAR POWER - Васильченко, Олександра; Котенко, Олег (SWorldJournal, 2022)
The article talks about the possibility of using thorium instead of uranium in nuclear power. The areas of possible application of thorium are considered and what benefits humanity will receive from this. The use of thorium as a contribution to reducing t